2013
DOI: 10.1177/0300060513476428
|View full text |Cite
|
Sign up to set email alerts
|

A review of statin use in patients with acute coronary syndrome in Western and Japanese populations

Abstract: Early high-dose statin therapy to reduce low-density lipoprotein cholesterol (LDL-C) is associated with improved cardiovascular outcomes in Western patients with stable coronary heart disease or acute coronary syndromes (ACS), but many patients remain undertreated and do not attain LDL-C treatment goals. Early statin therapy has also been shown to improve cardiovascular outcomes in Japanese patients with ACS, and pretreatment with high-dose statin prior to percutaneous coronary intervention has been shown to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…According to the current European guidelines, as well as the US guidelines, a treatment goal of LDL-C < 70 mg/dL is recommended [16, 17]. In spite of the emphasis of guidelines on the tight control of the LDL-C level, several surveys have shown that still a large number of patients remain undertreated and do not attain LDL-C treatment goals [11, 12, 27]. Similarly, our result is in line with that reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…According to the current European guidelines, as well as the US guidelines, a treatment goal of LDL-C < 70 mg/dL is recommended [16, 17]. In spite of the emphasis of guidelines on the tight control of the LDL-C level, several surveys have shown that still a large number of patients remain undertreated and do not attain LDL-C treatment goals [11, 12, 27]. Similarly, our result is in line with that reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Statins limit cholesterol synthesis and increase LDL-C catabolism. 64 They have demonstrated clear benefits in reducing morbidity and mortality in the secondary prevention of CAD but have been thought to be associated with decreased cognition because of low concentrations of LDL-C. However, a recent study by Rej et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, progress of patients after DES implantation is carefully observed with well-controlled drug compliance including anti-platelet agents [20]. In addition to these factors derived from the medical side, Japanese are different from Caucasian in the viewpoints of patients' lipid profiles due to genetic and environmental factors [34].…”
Section: Discussionmentioning
confidence: 99%